Dissimilar Metal Welding by Resistance Spot Welding of 6061 Aluminum Alloy /AISI 1006 Steel Using Zn and Sn Coating - Al-kinani, Ammar Y.; Alali, Muhaed (Journal of Petroleum Research and Studies, 2023)
This study was conducted to investigate the effect of welding parameters, and coating type on the weldability between 6061 aluminum alloy and AISI 1006 steel joints welded by the resistance spot welding technique. The mechanical properties, microstructure, and corrosion resistance were evaluated. The experimental tests used to evaluate the welded joint properties included a tensile shear test, microhardness test, microstructure examination, Energy dispersive X ray spectroscopy (EDS) analysis, and corrosion resistance test. However, Tin and zinc coating was utilized to improve the weldability of the joint. As a result, it was found that the maximum shear force for the welded joint without coating is 2.7 KN and increased to 4.24 KN when the use of coatings. For the microstructure characterization, a brazing-like joint was observed in the welded area that consists of a resolidified molten aluminum inside the weld nugget bonded with heat affected steel. Intermetallic compounds (IMC) of Fe - Al were detected at the joint interface by EDS analysis causing microcracks at the joint interface. Furthermore, Vickers microhardness varied across the joint due to the impact of welding heat and pressure on the base metals. Maximum hardness value was recorded in the thermo mechanical affected zone (TMAZ) at the steel side and the nugget zone consisted of aluminum with enhanced hardness due to the effect of Intermetallic compounds. Regarding the corrosion resistance, it was revealed that with increasing welding current, the corrosion rate increases due to the rise in the size of heat affected zones and nugget zone.